Blood Lipid Levels and the Severity of Guillain–Barré Syndrome: A Single-Center Retrospective Cohort Study - Yangrongzhuo Huang; Lina Feng; Yuhan Li; Hailing Zhou; Linglong Meng; Xuening Li; Juan Tang (Neurology Research International)
Conclusion: Elevated LDL and reduced ApoA are independent risk factors for GBS progression and cranial nerve involvement. Combined detection may aid early identification of high-risk patients. Dyslipidemia likely exacerbates GBS pathology through neuroinflammatory mechanisms, suggesting targeted lipid regulation as a potential therapeutic strategy.